Israel and the Church in the Perspective of Church History in Indonesia: Between Continuity and Contextualisation of God's People - Yusak Agus Setiawan; Rajiman Andrianus Sirait (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This article aims to explain the theological relationship between Israel and the Church as God's people, as discussed in biblical studies, and to relate it to the history and development of the Church in Indonesia. Using a qualitative-descriptive approach, this paper explores key theological concepts regarding Israel and the Church, examining how these understandings shape the Church’s mission, identity, and role. The study spans from the colonial era to the digital age, highlighting how historical and cultural contexts influence ecclesial expressions. The article argues that while the Church does not replace Israel as God's covenant people, it participates in God's redemptive plan through Christ. In the Indonesian context, the Church manifests its identity as God's chosen people by embracing local wisdom, cultural diversity, and a contextual mission. This dynamic relationship reflects the Church’s calling to live out its faith in Christ within a pluralistic society, contributing to nation-building and bearing witness to the Gospel in relevant and transformative ways.